The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/su12062237
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Risk Factors Affecting the Severity of Traffic Accidents on Spanish Crosstown Roads: The Driver’s Perspective

Abstract: Globally, road traffic accidents are an important public health concern which needs to be tackled. A multidisciplinary approach is required to understand what causes them and to provide the evidence for policy support. In Spain, one of the roads with the highest fatality rate is the crosstown road, a particular type of rural road in which urban and interurban traffic meet, producing conflicts and interference with the population. This paper contributes to the previous existing research on the Spanish crosstown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 41 publications
3
24
0
3
Order By: Relevance
“…As no similar studies have been found, making it impossible to compare the results obtained, it can be stated that the speed-reduction effect of the wider marks seen here is in line with the results of somewhat similar experiments about the effects of longitudinal speed reduction markings [26,27], and the consequences of implementing, or not, longitudinal road markings [29][30][31]. The speed-reducing effect may contribute to a reduction in the number of accidents associated with the implementation of wider longitudinal road markings [9,25,28] or the narrowing of lanes [6].…”
supporting
confidence: 87%
See 2 more Smart Citations
“…As no similar studies have been found, making it impossible to compare the results obtained, it can be stated that the speed-reduction effect of the wider marks seen here is in line with the results of somewhat similar experiments about the effects of longitudinal speed reduction markings [26,27], and the consequences of implementing, or not, longitudinal road markings [29][30][31]. The speed-reducing effect may contribute to a reduction in the number of accidents associated with the implementation of wider longitudinal road markings [9,25,28] or the narrowing of lanes [6].…”
supporting
confidence: 87%
“…These results may, indirectly, be associated with traffic speed-at low speed (with dense traffic) it is easier to keep the vehicle in the center of the lane than at high speed (with low traffic). Regarding the influence of the lane width in traffic accidents, Casado-Sanz et al [6] looked into 1064 accidents in the period 2006-2016 in two-lane rural highways in Spain, finding that the occurrence of fatal injury is greater in the wider lanes (45.80% in the lanes over 3.75 m wide, 41.40% in the lanes having a width under 3.25 m, and 32.30% in those of intermediate width).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the ANN model compared with the proposed Hybrid model. The Comparative performance of both models showed that the proposed model (Hybrid K means and random forest) performed better than the ANN model in terms of Precision, Recall, F1 score, Gu et al [21] PSO-SVM China -Xiao et al [52] SVM, KNN (Ensemble) I-880 data set 99.33% Castro et al [15] BN, JR8 and MLP DVSA-UK 72.39%, 72.02%, 71.70% Respectively Al-Radaideh et al [4] RF, ANN (backpropagation), SVM Uk 80.6%, 61.4%, 54.8% respectively Casado et al [14] LCC, MNL Spain -Wahab et al [51] MLP. SimpleCart, PART Ghana 72.16%, 73.45%, 73.81% respectively Sameen et al [40] MLP, BLR, RNN Malaysia 65.48%, 58.30%, 71.77% respectively Fentahun [18] J48, ID3, PART Ethiopia 81.21%, 81.01%, 81.18% Seid et al [42] HMR Ethiopia NA Abebe et al [1] DSA Ethiopia -Lytin et al [30] UBA Ethiopia - and Accuracy.…”
Section: Comparative Of Neural Network and Proposed Modelsmentioning
confidence: 99%
“…The generated noise has a significant health impact [35,36] such as sleep disturbance and anxiety [37]. In addition to that, the number of accidents happening can depend on the road network [38][39][40].…”
Section: Introductionmentioning
confidence: 99%